Lifetime occupation and physical function: a prospective cohort study on persons aged 80 years and older living in a community. Issue 7 (16th June 2006) - Russo, A; Onder, G; Cesari, M; Zamboni, V; Barillaro, C; Capoluongo, E; Pahor, M; Bernabei, R; Landi, F
Abstract : Background: Several studies have reported predictors for loss of mobility and impairments of physical performance among frail elderly people. Aim: To evaluate the relationship between lifetime occupation and physical function in persons aged 80 years or older. Methods: Data are from baseline evaluation of 364 subjects enrolled in the ilSIRENTE study (a prospective cohort study performed in a mountain community in Central Italy). Physical performance was assessed using the physical performance battery score, which is based on three timed tests: 4-metre walking speed, balance, and chair stand tests. Muscle strength was measured by hand grip strength. Lifetime occupation was categorised as manual or non-manual work. Results: Mean age of participants was 85.9 (SD 4.9) years. Of the total sample, 273 subjects (75%) had a history of manual work and 91 subjects (25%) a history of non-manual work. Manual workers had significant lower grip strength and physical performance battery score (indicating worse performance) than non-manual workers. After adjustment for potential confounders (including age, gender, education, depression, cognitive performance scale score, physical activity, number of diseases, hearing impairment, history of alcohol abuse, smoking habit, and haemoglobin level), manual workers had significantly worse physical function (hand grip strength: non-manual workers 32.5 kg, SE 1.4, manual workers 28.2 kg, SE 0.8; physical performance battery score: non-manual workers 7.1, SE 0.4, manual workers 6.1, SE 0.2). Conclusions: A history of manual work, especially when associated with high physical stress, is independently associated with low physical function and muscle strength in older persons.